Letter from Carl D. Duncan to Patricia Whiting, May 12, 1965 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan emphasizes to Whiting that she is free to give him honest criticism and outlines his schedule for the following day.